A123 DEFINING CROHN'S DISEASE STRICTURES USING INTESTINAL ULTRASOUND COMPARED TO HISTOPATHOLOGY. (4th March 2021) - Cooper, J; Koro, K; Wilson, S; Medellin, A; Ma, C; Novak, K L; Seow, C; Kaplan, G G; Panaccione, R; Lu, C
Abstract: Background: Fibrostenotic Crohn's Disease (CD) is a challenging phenotype often leading to surgical resection. Diagnostic imaging is an invaluable tool to diagnose CD strictures. MRE (Magnetic Resonance Enterography) is the most widely used modality for evaluating strictures, but is limited by access and cost. The current definition of strictures is based only on MRE or CT (computed tomography). Strictures are defined as increased bowel wall thickness (BWT), narrowed luminal apposition, and pre-stenotic dilation > 3cm according to CONSTRICT MR/CT expert consensus criteria. However, this definition has not been studied in intestinal US (IUS). IUS is a cost-effective, easily repeatable, and well-tolerated tool shown to have equal accuracy to MRE in diagnosing and monitoring CD. Aims: The objective of this study was to assess the utility of identifying strictures with IUS using CONSTRICT definition. Methods: In this retrospective pilot study, 30 of 80 CD patients who underwent small bowel resection (gold standard for stricture diagnosis) between 2015–2019 with IUS within 6 months prior to surgery were randomly identified for chart review. IUS was performed in a fasted state without oral contrast. Data extracted included confirmed stricture on resection specimens defined as having fibrosis and prestenotic dilation. Fistulizing disease was excluded. Student's t-tests, sensitivities, specificities, positive (PNV) and negative predictive values (NPV) were calculated for IUS in detecting strictures. Results: Of the 30 CD patients evaluated, 20 patients had fibrostenosis on pathology and IUS reports. Only 40% (8/20) met CONSTRICT criteria for stricture diagnosis on IUS, despite having a stricture on pathology. All patients had elevated BWT and luminal narrowing, but 60% (12/20) did not have prestenotic dilation > 3cm. Mean dilation was 2.9 cm (SD 1.38) and was significantly different from the mean stricture diameter of 1.3cm (SD 0.59 cm, p=0.0001, 95% CI: 0.9–2.2). Mean BWT was 8.7 mm (SD: 2.5, range 5–15) where normal is < 3mm, and mean luminal apposition was 2.3 mm (SD 1.2, range 0.2–5.8mm). IUS has a sensitivity of 95.2% (95% CI: 76.2 - 99.9%), specificity of 66.7% (95% CI: 29.9 - 92.5%), PPV of 87.0% (95% CI: 72.5–94.4), and NPV of 85.7% (95% CI 45.6–97.7%) in detecting strictures when compared to gold standard. Conclusions: CONSTRICT criteria for diagnosing fibrostenotic CD on CT/MR may not be applicable to IUS. In this study, only 40% of patients met criteria despite having histologic confirmed strictures. Thus, perhaps additional criteria of stricture diameter < 50% of prestenotic dilation size is most appropriate for IUS. This pilot study provides the initial data to delineate an IUS stricture definition for future validation and to inform both clinical practice and trial design. Funding Agencies: None